Student’s Perceived Service Quality and Satisfaction: The Case of Dining Environment at INTI International University - Hung, Hwee Li (2010)
The study was conducted to report the service quality provided by the INTI Cafeteria which provides dining services to students and employees of INTI (INTI International University) as one of the non-academic supporting facilities. Based on the comments received from students, the study was conducted to find out in detail about the level of satisfaction of students who use the dining places and their expectation of a good dining place. This study applied the famous SERVQUAL’s five dimensions of service quality (Tangibility, Reliability, Responsiveness, Assurance and Empathy) to capture the service quality provided by INTI Cafeteria. Service Gap Analysis shown a negative direction of the total mean score (-1.24) of 7 –Point Likert Scale from 22 attributes that indicated the cafeteria still need to upgrade the services to meet the customer expectation. The ranking of expectation and perception given by students was sorted and documented. The study highlighted the areas that need improvement and strong points of INTI Cafeteria. Statistical Package for Social Science (SPSS) tool was used to test the given hypothesis on SERVQUAL dimensions that applied to INTI Cafeteria’s dining environment. This report with several potential recommendations in improving and monitoring dining services will be very useful to the management and outlets owners of the dinning places at INTI to upgrade their tangible and intangible service elements to help INTI to gain a better competitive position in educational business. It will gain public recognition in providing good dining services, attention to dinning safety and quality that directly link to the public perception on INTI who care about their students.